Oxidative stress and inflammation mediate the association between elevated oxidative balance scores and improved sleep quality: evidence from NHANES - Zhang, Qu; Yi, Jing; Wu, Yemei (Frontiers in Nutrition, 2024)
Background The association between oxidative stress, as measured by the Oxidative Balance Score (OBS), and sleep quality remains unclear. The primary objective of this investigation was to clarify this relationship and to explore the potential involvement of oxidative stress and inflammation. Methods Data from 15,198 participants in the National Health and Nutrition Examination Survey 2007–2014 were analyzed. Sleep quality indicators, including sleep disorder, trouble, and duration, were assessed. The OBS, comprising information on 16 dietary nutrients and 4 lifestyle factors, was then calculated. Multivariable logistic and linear regression models were employed to investigate the correlation between OBS and sleep quality. Additionally, mediation analyses were conducted to evaluate the potential effects of oxidative stress and inflammation. Results We demonstrated a correlation between an elevated OBS and reduced sleep disorders (OR, 0.72; 95% CI, 0.58–0.91; p = 0.0055), reduced sleep trouble (OR, 0.81; 95% CI, 0.69–0.96; p = 0.0174), and prolonged sleep duration (β 0.009; 95% CI, 0.0002–0.0160; p = 0.015) when comparing the highest and lowest tertiles. Dietary factors exhibited autonomous correlations with sleep duration, whereas lifestyle factors displayed independent associations with sleep trouble and sleep disorders. Moreover, the relationships between OBS and both sleep disorders and trouble were influenced by albumin, γ-glutamyl transferase, total bilirubin, and white blood cells, with combined mediation effects of 34.66 and 29.54%, respectively (both p < 0.001). Sensitivity analyses revealed a significant association between OBS and sleep disorder (p < 0.001). Conclusion This study revealed a positive correlation between an elevated OBS and improved sleep quality, manifested by decreased sleep disorders, mitigated sleep trouble, and prolonged sleep duration. This is potentially mediated by oxidative stress and inflammation. Therefore, the study underscores the importance of adopting a diet rich in antioxidants and healthy lifestyle choices to address sleep-related concerns, providing a novel avenue for enhancing overall sleep quality.